Efektivitas Anggaran Penanganan Sampah Pasca Covid-19 Studi Pada Dinas Lingkungan Hidup Kabupaten Bengkalis Tahun 2020 - Husni Mubarak; Liska Rahmadani (Politeknik Negeri Bengkalis, 2022)
During the Covid-19 period, various activities and activities were affected and underwent changes, including changes in waste management. This study aims to look at the role of the Bengkalis Regency Environmental Service (DLH) in managing the waste budget during the COVID-19 period. The budget has an important role for an organization, both government and private. Budget is a management control tool to achieve organizational goals. Local governments have an important role in planning and realizing budgets. The purpose of this study was to find out (1) the Budget Mechanism of Waste Handling in Bengkalis Regency. (2) Effectiveness of the Waste Handling Budget at the Environmental Service during the Covid 19 era. The type of data used in this study is qualitative data and calculation of effectiveness measurements. The results showed that the level or criteria for budget effectiveness for waste handling activities in 2020. The level of effectiveness in 2020 was 99.29% with effective criteria. To increase the effectiveness of budget realization, it is necessary to coordinate and cooperate between parties and make good planning and implementation to achieve maximum results.